Mapping of Somatostatin-28 (1-12) in the Alpaca (Lama pacos) Brainstem - De Souza, E (2015)
Using an indirect immunoperoxidase technique, we studied the distribution of cell bodies and fibers containing somatostatin-28 (1-12) in the alpaca brainstem. Immunoreactive fibers were widely distributed throughout the whole brainstem: 34 brainstem nuclei/regions showed a high or a moderate density of these fibers. Perikarya containing the peptide were widely distributed throughout the mesencephalon, pons and medulla oblongata.